Analisis Kesehatan Keuangan dan Prediksi Kebangkrutan Perusahaan PT Pertamina (persero) Periode 2017-2020 - Achtikah Achtikah; Endang Sri Wahyuni (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2021)
The purpose of this study is to determine the financial health of pertamina (persero) and predict the company’s bankruptcy from 2017 to 2020 based on Surat Keputusan Menteri BUMN Nomor:KEP-100/MBU/2002 and Altman Z-Score Analysis. The type of data used in this study is company’s audited financial statement for the period 2017-2020. Data Collection technique in this study is to analyze the company’s audited financial statement from 2017-2020. The result showed that based on the ratio in SK Menteri BUMN Nomor:KEP-100/MBU/2002 based on the financial aspect with indicators namely ROE, ROI, Cash Ratio, Current Ratio, Collection Periods, Inventory Turnover, TATO, and Total Equity to Total Assets, the level of soundness of the company PT Pertamina (persero) from 2017 to 2020 it is in the unhealthy category because the total score of the health assessment level obtained from these 8 indicators is less than 65 from the total score it should be, which in 70. The prediction of PT Pertamina (persero) bankruptcy, the average Z-Score analysis value in 2017 to 2019 up 2,0 with the category of a zone of ignorance or grey area, while in 2020 when during the corona pandemic the lowest score of 1,82 in the category of a zone of ignorance or grey area, therefore the company PT Pertamina (persero) is expected to be able to improve the level of financial health and financial performance so that the company can achieve a healthy predicate or category.